Transmembrane Amino Acid Transporters in Shaping the Metabolic Profile of Breast Cancer Cell Lines: The Focus on Molecular Biological Subtype - Elena I. Dyachenko; Lyudmila V. Bel’skaya (Current Issues in Molecular Biology)
Amino acid metabolism in breast cancer cells is unique for each molecular biological subtype of breast cancer. In this review, the features of breast cancer cell metabolism are considered in terms of changes in the amino acid composition due to the activity of transmembrane amino acid transporters. In addition to the main signaling pathway PI3K/Akt/mTOR, the activity of the oncogene c-Myc, HIF, p53, GATA2, NF-kB and MAT2A have a direct effect on the amino acid metabolism of cancer cells, their growth and proliferation, as well as the maintenance of homeostatic equilibrium. A distinctive feature of luminal subtypes of breast cancer from TNBC is the ability to perform gluconeogenesis. Breast cancers with a positive expression of the HER2 receptor, in contrast to TNBC and luminal A subtype, have a distinctive active synthesis and consumption of fatty acids. It is interesting to note that amino acid transporters exhibit their activity depending on the pH level inside the cell. In the most aggressive forms of breast cancer or with the gradual progression of the disease, pH will also change, which will directly affect the metabolism of amino acids. Using the cell lines presented in this review, we can trace the characteristic features inherent in each of the molecular biological subtypes of breast cancer and develop the most optimal therapeutic targets.